Exploring the elements of audience engagement in job advertising of job search website in Malaysia / Zanariah Abdul Rahman ... [et al.] - Abdul Rahman, Zanariah; Othman, Akmal Aini; Mat Din, Syaidatul Zarina; Abdul Rahman, Norsahira (UiTM Cawangan Johor, 2019)
Recently, Internet or social media has been the popular choice for companies to develop their business strategies. Social media is not used for communication tool or for entertainment only but also plays an important part in marketing strategy as well as a recruiting platform. A job search websites agency has tried various new strategies to drive traffic from Facebook to their job platform. Although Facebook has billions of users, some website advertisements on Facebook are not attractive enough to attract audience engagement. There are many elements in job advertising that have caused the audience whether to engage or not with the ads. Moreover, not many studies have been done on evaluating the elements in job advertising, especially in Malaysia. Therefore, the researchers want to assess the types of audience engagement towards job advertising in Facebook and to explore the elements in job advertising that are able to increase the audience engagement. To gain deep insight about this topic, the researchers conducted an exploratory research where audiences were interviewed about their engagement with the job advertising especially in Facebook. The study revealed that audiences who mostly 'like' the ads will share it with other people. Besides interactive functions, colours and fonts of the ads are also important elements to determine audience engagement.